Evaluación de Riesgos Mayores en el Edificio Administrativo de la Universidad Nacional de Chimborazo. - Peralta Valverde, Noemí Karina (2013)
The reality is that most public and private institutions in our country lack a safety plan for their workers that would allow them to be trained for a possible emergency that may arise during the workday. It is known that in recent years, workplace accidents and occupational diseases have increased rapidly, according to statistics. The focus of this study is to determine the major risks present at the National University of Chimborazo and propose an Emergency Plan. To this end, an evaluation was carried out using methods that allowed us to determine and classify the degree of hazard, such as the Thermal Load Method, the Mésseri Method, and the Meippee Method. This is due to the lack of internal policies for safety, prevention, and environmental protection in all workplaces. Therefore, the Ministry of Labor Relations, along with the Occupational Risk Department of the Ecuadorian Social Security Institute (IESS), is conducting inspections to ensure compliance with laws and regulations regarding occupational risk prevention. The importance of an Emergency Plan is very important tohighlight that the University is complying with current legal regulations; for the achievement of these objectives, the University already has the Labor, Occupational Health and Environmental Management Unit.